(untitled) (Revista Innova Educación, 2019)
The purpose of the research is to describe the perception that students show regarding the climate of the university classroom, the population and study sample is composed of students of the Secondary School Professional School, the type of research is descriptive, the design is descriptive, diagnostic , the technique used is the survey, the questionnaire is called university classroom climate, being of the licker type, which consists of a set of assertive items expressed in categories that were answered by the respondents. The information collected in statistical tables and graphs is systematized, using the percentage measure in its reading and interpretation, considering the scales of agreement (A) and completely in agreement (CA), the results show us that regarding the dimensions: cohesion, satisfaction , personalization, task orientation, innovation, evaluation and class management, a percentage measurement of less than 62% is shown that corresponds to the dimension oriented to the task and a percentage measure greater than 79% corresponding to the personalization dimension. In sum, the dimensions under study show a favourable classroom climate.